The Neuroeducation Training of Students in the Degrees of Early Childhood and Primary Education: A Content Analysis of Public Universities in Andalusia - Paula Peregrina Nievas; Carmen del Pilar Gallardo-Montes (MDPI AG, 2023)
Educational neuroscience presents a broad view of what learning is and how and when it occurs. Consequently, neuroeducation offers improved strategies for understanding and developing the teaching-learning process. It is, therefore, essential that teachers and students are trained in neuroeducation, given the current knowledge in this field. Consequently, this study aims to reflect on the training in neuroeducation received by undergraduate students studying early childhood and primary education and to find out how the teaching of neuroeducation is approached in the universities of the eight Andalusian provinces. As methodology, a content analysis was made, which allowed us to transform qualitative data into quantitative data. The categories analysed were "Neuroeducation", "Metacognition", "Cognitive processes" and "Cognition". The study plans for the 2022/2023 academic year were considered. The analysis results of these plans showed that, despite the relevance of neuroeducation in the educational context, the study plans barely addressed this subject. This suggested that the training received by future teachers was not enough to enable them to make the most of neuroscience and neuroeducation considerations.